Elimination of interlayer Schottky barrier in borophene/C4N4 vdW heterojunctions via Li-ion adsorption for tunneling photodiodes. Issue 12 (8th March 2021) - Zheng, Cancan; Zhou, Cong; Shi, Man; Li, Haiyan; Dou, Nianxi; Ma, Zhihao; Xia, Feifei; He, Yuanyuan; Zhao, Jianwei
Abstract : The adsorption of Li-ions on the bottom site contributes to improve the photodetectivity and photoresponsivity in B/C4 N4 vdW heterojunction photodiode, owing to the elimination of interlayer Schottky barrier. Abstract : The nonzero interlayer Schottky barrier leads to a compromise between photodetectivity and photoresponsivity in photodiodes based on vdW heterojunctions. Seeking for the appropriate vdW heterojunction with Ohmic contact and a high tunneling barrier is of great significance to realize high-performance photodiodes. We built borophene/C4 N4 (B/C4 N4 ) vdW heterojunctions with a reduced interlayer Schottky barrier, by combining density functional theory and non-equilibrium Green's function. The adsorption of Li-ions can further tune its Schottky contact into n-type Ohmic contact. The electronic properties of the Li-ion-adsorbed B/C4 N4 vdW heterojunction, including the separation of hole–electron pairs, the work function, as well as the effective mass of carrier, can be modulated by changing the adsorption site of Li-ions. B/C4 N4 /Li shows the most excellent absorbing capability of the infrared illumination and the strongest negative rectification, due to the highest interlayer tunneling barrier. The bottom surface of the C4 N4 sublayer is the optimal adsorption site of Li-ions, for the potential application of B/C4 N4 vdW heterojunctions in tunneling photodiodes. Our work unveils the great significance of Li-ion adsorption in modulating the interlayer Schottky and tunneling barriers in vdW heterojunctions, thus improving their device performance.